CREATIVE VECTORS IN VARLAM SHALAMOV’S POETRY AND PROSE - Meskin,; Agarwal, Shraddha (Revista Inclusiones, 2020)
The article deals with the topic of Varlam Shalamov’s creative search in poetry and prose and his transition from realism with a fraction of romanticism to factual literature. In this context, the drastic change in the author’s attitude towards the purpose of literary art and human nature are explained and the significant change in the pathos in a number of his lyrical and epic works is discovered. The analysis of many of his works reveals that Shalamov treated classical traditions critically and selectively while the poetics of his works changed substantially depending on the goals the master set for himself.